Miscarriage : an exploration of women's experience : a qualitative study - Watson, Julia Margretha Garland (Rhodes University, Faculty of Humanities, Department of Social Work, 2004)
Miscarriage can result in significant psychological distress to women. However, many women experience a cultural norm which attributes minimal meaning to the loss. This is reflected in the lack of support experienced from interaction with both medical professionals and those within the individual's social context. This qualitative study reports on the unique experiences of six South African women; their experience of other's reactions to their miscarriage; and their recommendations for better coping with the experience. Data was gathered using one semi-structured interview. Data reduction and analysis followed using a four-stage model of thematic outlines, coding, and comparisons (Marshall and Rossman 1998:152; Marck and Field 1994:9). The objective of the analysis sought to compare the themes generated by the actual data collected with those described in other studies. In this way the findings of the study are generalisable to a larger population and allows for a greater sense of representivity (Silverman 1994:160). Comparisons were made between the women's experiences, as told by them, and Bowles' identification of the Four Domains of Miscarriage Distress Symptoms (2000). The women viewed psychological support as essential in the process of coping; and acknowledgement of their loss as being the loss of a child, as a strong determinant of coming to terms with the loss. A strong need to have support from other women who had shared the experience was voiced. Recommendations for improved intervention are made. In short the core recommendations are: the provision of patient follow-up; the provision of written material; and, specialist training for those working in the area of pregnancy loss.
Keywords: Miscarriage -- Psychological aspects; Loss (Psychology); Bereavement -- Psychological aspects; Infants -- Death -- Psychological aspects; Fetal death -- Psychological aspects